The Influence of the 7P Strategy on Passenger Satisfaction and Loyalty at Terminal 3 Soekarno-Hatta Airport: An Operations Management Approach - Namira, Maryam; Pasaribu, Rina (International Journal of Science, Technology & Management, 2024)
The COVID-19 pandemic highlighted the dependence of aeronautical revenue on external factors, making it crucial to increase non-aeronautical revenue. Major global airports like Changi and Incheon have achieved this revenue balance, but Indonesia's five largest airports, including Soekarno-Hatta and I Gusti Ngurah Rai, have not. Balanced non-aeronautical revenue can cover investment and promotional costs without relying on aeronautical income. Soekarno-Hatta, as a major hub, still has limited tenants, and retail and F&B revenues in Terminal 3 have significantly declined. To address this issue, reducing passenger queue times through digitalization and improving airport facilities has become a primary focus. This research uses 400 questionnaires analyzed with structural equation modeling (SEM) using SmartPLS 4.0 software. The focus is on identifying the influence of the 7P—covering product (tenant variety), price, promotion, place, people (service quality), process (self check-in and immigration autogates), and physical evidence (cleanliness and terminal design)—on customer satisfaction and loyalty in Soekarno-Hatta's Terminal 3. Digitalization, such as self check-in and immigration autogates, is expected to reduce queue times, providing passengers with more time to shop and thus increasing non-aeronautical revenue. This study aims to find the most significant factors affecting customer satisfaction and customer loyalty at the airport. The results indicate that product, process and physical evidence have a positive and significant impact on both customer satisfaction and customer loyalty.